Synthesis and Effect of Physical Aging on Gas Transport Properties of a Microporous Polyimide Derived from a Novel Spirobifluorene-Based Dianhydride - Ma, Xiaohua; Ghanem, Bader; Salines, Octavio; Litwiller, Eric; Pinnau, Ingo (ACS macro letters, 2015)
A novel generic method is reported for the synthesis of a spirobifluorene-based dianhydride (SBFDA). An intrinsically microporous polyimide was obtained by polycondensation reaction with 3,3′-dimethylnaphthidine (DMN). The corresponding polymer (SBFDA-DMN) exhibited good solubility, excellent thermal stability, as well as significant microporosity with high BET surface area of 686 m2/g. The O2 permeability of a methanol-treated and air-dried membrane was 1193 Barrer with a moderate O2/N2 selectivity of 3.2. The post-treatment history and aging conditions had great effects on the membrane performance. A significant drop in permeability coupled with an increase in selectivity was observed after long-term aging. After storage of 200 days, the gas separation properties of SBFDA-DMN were located slightly above the latest Robeson upper bounds for several gas pairs such as O2/N2 and H2/N2.